Design of Integrated Geothermal- Solar Based System for Multigenerational Needs in a District Energy System Application - Alimoradiyan, Hamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The current thesis proposes an integrated geothermal based multi-generation system including the triple effect LiBr/water absorption system (TEAS), organic Rankine cycle (ORC), air-conditioning system (dehumidification with cooling) and an electrolyzer. The aim of this system is to supply six outputs comprising heating, cooling, dry air, hot water, hydrogen, and power. All the simulations are done by Engineering Equation Solver software (EES). By inputting 500K geothermal water, the energetic and exergetic overall utilization factors (Ɛen and Ɛex) for the completely multi-generation cycle would be 2.467 and 1.097, respectively. A parametric study was conducted indicating that a rise in the environment (ambient) temperature from 295K to 320K leads to an accumulative trend for exergetic coefficient of performance (COPex) while energetic coefficient of performance (COPen) remains constant in TEAS. While, the evaporator temperature rises from 274K to 279K, there is a downward trend for COPen and COPex (from 1.491 to 1.479 and 0.3525 to 0.3145, respectively) as well as Ɛen and Ɛex. By raising the geothermal temperature from 400K to 500K, Ɛen and Ɛex will increase from 2.354 to 2.467 and from 1.055 to 1.105, respectively. Moreover, the rise in geothermal temperature will upsurge the rate of hydrogen production as well as the heat rate in hot water production from 0.004873L/s to 0.005944L/s and from 8.365kW to 112.9kW, respectively. Moreover, environmental impacts, as one of the most designing parameter, are analyzed to find the system irreversibility (exergy destruction) and exergy losses. The parametric simulation is done to check the system in term of environmental suitability. In addition, a comparative study shows that using multi-generation cycle with higher COPen and COPex in comparison with conventional systems is more feasible to design for reaching the six outputs. Keywords: Geothermal, Multi-generation, Energy, Exergy, Overall Utilization Factor, Exergoenvironmental Impact Factors.

Öz: Bu çalışma çoklu jenerasyon sistemi ile üçlü etkili LiBr/su absorbsiyon sisteminin (TEAS) birleştirilmiş organik Rankin döngüsü (ORC), klima sistemi ( soğutma ile nem alma ) ve elektrolizer ile jeotermal tabanlı sistemlerin birleştirilmesini öngörmektedir. Bu sistemin amacı elde edilmesidin adet sonucun: ısıtma, soğutma, kuru hava, sıcak su, hidrojen ve gücün. 500K derecede jeotermal suyun enjekte edilmesi ile genel enerjik ve ekzerjik kullanım faktörleri (Ɛen ve Ɛex) sırası ile 2.467 ve 1.097 olacaktır. Üçlü etkili LiBr/su absorbsiyon sisteminin (TEAS) yapılan parametrik çalışma çevre ısısının 295K den 320K’e çıkması ekzerjik performans katsayısının (COPex) arttığını ancak enerjik performans katsayısının (COPen) ise sabit kaldığını göstermiştir. Dolayısı ile çevre sıcaklığı arttığında Ɛen sabit kalırken değişen her jeotermal kütle akışında Ɛen artacaktır, Bunun yanında buharlaştırıcı sıcaklığı 274K den 279K’e arttığında COPen ve COPex ( 1.491 den 1.479’a ve 0.3525 den 0.3145’e ) ayrıca Ɛen ve Ɛex sırası ile azalır. Soğutma yükü de 413.18kW’dan 410.4kW değerine düşerken klima sisteminde yoğunlaşan su miktarı artmaktadır. Jeotermal sıcaklığı 400K den 500K’e yükseltmekle Ɛen 2.354 den 2.467 ye ve Ɛex 1.055 den 1.105 ye sırası ile artacaktır. Ayrıca jeotermal sıcaklıktaki yükselme hidrojen üretim oranı 0.004873L/s den 0.005944L/s ye, sıcak su üretimindeki ısı oranını 8.365kW dan 112.9kW’a artıracaktır. Bunların yanında çevre etkisi de en önemli tasarım parametrelerinden biridir ve sistem geridönüşümsüzlüğünü ( ekzerji imhası ) ve ekzerji kayıplarını bulmak için analiz edilmiştir. Sistemin çevresel uygunluğu için parametrik simülasyon yapılmıştır. Ek olarak yapılan mukayese çalışması göstermiştir ki yüksek COPen ve COPex li çoklu generasyon döngüsü konvansiyonel sisteme göre istenen altı sonuca varmada daha uygulanabilir görülmektedir. Anahtar kelimeler: Jeotermal, Çoklu jenerasyon, Enerji, Ekzerji, Genel kullanım faktörü ve Ekzergoçevre faktörü.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2016. Supervisor: Assoc. Prof. Dr. Hasan Hacışevki.
Keywords: Mechanical Engineering; Solar Energy; Geothermal; Multi-generation; Energy; Exergy; Overall Utilization Factor; Exergoenvironmental Impact Factors